ANALISIS EFISIENSI DAN KARAKTERISTIK DAYA OUTPUT DC PADA SISTEM PEMBANGKITAN LISTRIK TENAGA SURYA SKALA INDUSTRI - Ruben William Pasaribu; Hartono; Valentino Pahotan Simamora; Nadia Nazarina Putri (SIPARSTIKA: Jurnal Ilmiah Ilmu-Ilmu Teknik, 2026)
On-grid Solar Power Plants (PLTS) are implemented in the industrial sector to improve energy efficiency. However, PLTS systems often experience differences between the design capacity based on Standard Test Condition (STC) and the actual output power due to environmental factors and technical losses. This study aims to analyze the DC output power (PDC) and efficiency of an on-grid PLTS system at Warehouse 1 PT XYZ. The research used a descriptive quantitative approach through direct observation and electrical measurements on a 356.4 kWp PLTS system consisting of 660 CS6W-540MS modules and 33 strings. Measurements were conducted every 30 minutes from 10:00 AM to 2:00 PM on March 24, 2026. The results showed that the DC voltage decreased from 809 V to 781.6 V, while the DC current increased from 237.93 A to 335.28 A due to temperature and solar irradiance. The highest output power generated was 262.05 kW with a maximum efficiency of 73.53% at 12:30 PM. The average efficiency of 64.33% indicates that the PLTS performance is still affected by power losses and operational conditions.